2005
DOI: 10.1007/s11745-005-1448-3
|View full text |Cite
|
Sign up to set email alerts
|

A rapid method for the quantification of fatty acids in fats and oils with emphasis on trans fatty acids using fourier transform near infrared spectroscopy (FT‐NIR)

Abstract: A rapid method was developed for classifying and quantifying the FA composition of edible oils and fats using Fourier Transform near infrared spectroscopy (FT-NIR). The FT-NIR spectra showed unique fingerprints for saturated FA, cis and trans monounsaturated FA, and all n-6 and n-3 PUFA within TAG to permit qualitative and quantitative comparisons of fats and oils. The quantitative models were based on incorporating accurate GC data of the different fats and oils and FT-NIR spectral information into the calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 41 publications
1
94
1
Order By: Relevance
“…In the factorized analysis, the average FT-NIR spectra for samples of fish oils or ethyl esters were obtained and chemometric analysis was performed to generate the classification reference models [24]. The differences between the average spectra were then presented as vectors, which are mathematical expressions used to quantify changes and differences between data sets.…”
Section: Ft-nir Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the factorized analysis, the average FT-NIR spectra for samples of fish oils or ethyl esters were obtained and chemometric analysis was performed to generate the classification reference models [24]. The differences between the average spectra were then presented as vectors, which are mathematical expressions used to quantify changes and differences between data sets.…”
Section: Ft-nir Measurementsmentioning
confidence: 99%
“…Azizian and Kramer [24][25][26] have demonstrated the use of FT-NIR for FA profiling of edible oils, including those containing trans FA. The same authors also showed that the quantitative analysis model developed was dependent upon the scanning temperature and the nature and quantity of minor constituents in the sample matrix, such as solvent [27] and sterols [28].…”
Section: Introductionmentioning
confidence: 99%
“…It is produced in the rumen through microbial biohydrogenation of linoleic acid and in tissues by delta-9 desaturation of rumen-derived transvaccenic acid ( t11 -FA 18:1) ( 5 ). In contrast, t9,t11 -CLA is the predominant isomer found in dietary oils, as it is generated during partial hydrogenation of vegetable oils and oil refi ning ( 6,7 ). Several data from in vitro and animal studies show that dietary CLAs are benefi cial and infl uence the progression of several diseases, including cardiovascular and infl ammatory diseases and cancer (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Different grades of Canadian beef would, therefore, likely be too inconsistent to allow for enrichment claims as is. The development and use of rapid analytical methods (e.g., Azizian and Kramer 2005;Aldai et al 2007) would prove useful in sorting carcasses with higher concentrations of beneficial fatty acids. In addition, dependent on the levels required, development of dietary and management strategies to consistently enrich beneficial fatty acids would also be of benefit.…”
Section: Variation In Fatty Acid Compositionmentioning
confidence: 99%